How Student Worksheets Based Metacognitive can Improve Learning Outcomes on Material Price Index and Inflation? - Jannah, Royhatul; Surjanti, Jun; Kurniawan, Riza Yonisa (Journal Intellectual Sufism Research (JISR), 2020)
The purpose of this paper is to improve student learning outcomes. This study is a Research and Development (R&D) using the 4D model Thiagarajan which includes stages Define, Design, Develop, and Disseminate but the Disseminate stage is not carried out. The findings showed that the feasibility of the material, language, evaluation, and graphics of 87%, 85%, 85%, 87% with a very decent category. The average N-gain score got a score of 0.6 categorized as moderate and classical completeness of student learning outcomes is 90%. While the results of the responses of students get an average percentage of 90,4% categorized as very feasible. Improved learning outcomes can be obtained using MMPII worksheets which include metacognitive features namely planning, monitoring, and evaluating. This study uses limited trials that were conducted on 20 students of XI IPS class Kanjeng Sepuh Senior High School.